Penerapan Model Pembelajaran Problem Based Learning Dipadu Metode Debat Terhadap Kemampuan Berargumentasi - Netti Marini; Berlian Romanus Turnip; Dea Puspita (Journal on Education, 2023)
This study aims to determine the forms of technological influence in the digital era on the character of respect and courtesy of students and character education strategies that are carried out to minimize the negative influence of technology and the obstacles faced by the school. This study uses a qualitative approach, with a descriptive qualitative research type. The data collection techniques used are interviews, observation, and documentation. While data analysis through three techniques, namely data reduction, data presentation, and drawing conclusions. And checking the validity of the data is done by technical triangulation and source triangulation. The results of the study show that the impact of technology on student character includes the impact on students' ways or patterns of communication, the impact on student attitudes and behavior, and the impact on student attitudes in learning. The character education strategy carried out by schools in minimizing the influence of technology on the character of respect and courtesy of students is carried out through self-development programs, integration in subjects, and school culture.